A tandemly repetitive centromeric DNA sequence of the fish Hoplias malabaricus (Characiformes : Erythrinidae) is derived from 5S rDNA - Martins, Cesar [UNESP]; Ferreira, Irani Alves; Oliveira, Claudio; Foresti, Fausto; Galetti, Pedro Manoel (Springer, 2006)
A substantial fraction of the eukaryotic genome consists of repetitive DNA sequences that include satellites, minisatellites, microsatellites, and transposable elements. Although extensively studied for the past three decades, the molecular forces that generate, propagate and maintain repetitive DNAs in the genomes are still discussed. To further understand the dynamics and the mechanisms of evolution of repetitive DNAs in vertebrate genome, we searched for repetitive sequences in the genome of the fish species Hoplias malabaricus. A satellite sequence, named 5SHindIII-DNA, which has a conspicuous similarity with 5S rRNA genes and spacers was identified. FISH experiments showed that the 5S rRNA bona fide gene repeats were clustered in the interstitial position of two chromosome pairs of H. malabaricus, while the satellite 5SHindIII-DNA sequences were clustered in the centromeric position in nine chromosome pairs of the species. The presence of the 5SHindIII-DNA sequences in the centromeres of several chromosomes indicates that this satellite family probably escaped from the selective pressure that maintains the structure and organization of the 5S rDNA repeats and become disperse into the genome. Although it is not feasible to explain how this sequence has been maintained in the centromeric regions, it is possible to hypothesize that it may be involved in some structural or functional role of the centromere organization.
Keywords: 5S rDNA; 5S rDNA variant; centromeric DNA; fish; Hoplias malabaricus; satellite DNA